The Everyday Life of Franz Joseph II Silva-Tarouca and His Family in the First Half of the 20th Century (Theatrum historiae, 2025)
The article will look into a history of everyday life of a nobleman in the era of the First Czechoslovak Republic. For this purpose, the figure of Count František Josef II Silva-Tarouca (1858–1936) and his family was chosen. Unlike his younger brother Arnošt Emanuel Silva-Tarouca, this nobleman did not achieve any significant political fame. His figure is remarkable in view of the variety of his private activities. Like many other members of aristocratic society, the Silva-Tarouca family had to cope with a number of changes after 1918. We can speak of him as a gifted painter, horse breeder, amateur archivist, or historian. After the end of the First World War, the family faced a number of financial difficulties, which son Egbert Silva-Tarouca decided to solve by modernising the estate. However, his investment in modernisation proved unsuccessful and led to the family’s forced departure from the chateau in Čechy pod Kosířem.
Keywords: Everyday life; Lifestyle; First Czechoslovak Republic; Aristocrat; Silva-Tarouca